Timor-Leste : Education Since Independence from Reconstruction to Sustainable Improvement - World Bank (Washington, DC, 2013)
Before Timor-Leste regained its independence on May 20, 2002, the transitional administration consulted with the East Timorese people on their aspirations for the future. Seven out of ten people cited education as their top national priority. The first National Development Plan made education a cornerstone of its strategy to alleviate poverty and facilitate economic growth. This sector study on education is a response to the aspirations of the people of East Timor and to its government's priorities. The study provides analytical support for medium-term policy options to expand coverage, raise internal efficiency and student achievement, and improve sectoral and expenditure management. At the most fundamental level, the government's target is to reach the Millennium Development Goals of gender parity in enrollment by 2005 and universal enrollment in and completion of primary education by 2015. This study focuses mainly on primary education with little coverage of youth, the labor market, or tertiary education. The study begins by discussing the evolution of the education system and how historical legacies shape current conditions. It examines the barriers to access, efficiency, and quality as well as the policies needed to remove them. It also discusses institutional issues and the medium-term public expenditure framework and assesses the options for improving sectoral management and achieving financial sustainability.